Diálogos cercados: comunicação entre produtores de pesca do cerco e IPIMAR - Farinha, Sandra Isabel Cristóvão (2005)
This study describes the communicational reality between purse seine fishermen and scientists, and explores the issues which divide them or those that unite them. The nature of the Common Fisheries Policy and the context of the Portuguese fisheries sector, with purse seine fishing in particular, demonstrate the changes occurring in Portugal as it undergoes integration into the European Union. Portuguese fishermen and scientists occupy different worlds, and communication between them is largely limited to the scientific information released by the National Institute for Agriculture and Fisheries (IPIMAR), and to occasional meetings which are held at this institute. The fishermen are not aware of any need to share their knowledge, and little use is made of such information. A successful coming together of these two groups occurred in 1997, when it became necessary to implement a plan of action concerning sardine resources. However, the concerns of the fishermen differ from those of the scientists; for the former, lack of manpower and problems related to commercialisation are the central questions, whilst the latter wish to monitor the behaviour of the stock in order to aid decision making at management level. Between these quite different cultures it is natural that the language used is also different, a consequence of which is the fact that the information given to the fishermen is often misunderstood. The data presented in this study were obtained at the beginning of 2004, and the results show that a constructive dialogue between scientists and fishermen is possible, but only if the information flows in mutually-understood language, and where both parties have something to gain by the sharing of information.